How do constitution-making processes fail? The case of Chile’s Constitutional Convention - Verdugo, Sergio; García Huidobro, Luis Eugenio (Cambridge University Press, 2023)
This introduction to the symposium ‘How do Constitution-Making Processes Fail? The Case of Chile’s Constitutional Convention (2021–22)’ situates the project in the field of constitution-making, provides context regarding the Chilean case, summarizes some possible explanations for the failure, and describes how each article contributes to the symposium as a whole.
Keywords: Chilean Constitution; Constitution-making; Activation failures; Constitutional Referendum; Constitutional Convention